The propensity of risk-taking and financial efficiency: Exploring the role of management accounting systemdevidence from the manufacturing sector - Sarfaraz Javed; Mustafa Malik (Cogent Business & Management, 2021)
This study aimed to know the impact of management accounting systems on firm financial efficiency while considering the CEOs risk-taking propensity. The Data was collected with the help of a self-administered questionnaire-based survey from the manufacturing sector of India. Used purposive sampling technique to collect data from 338 respondents. Results have shown that the broad scope management accounting system and integrator's impact is insignificant on firm financial efficiency. In contrast, the effects of timeline and aggregation are significant on firm financial efficiency. Simultaneously, the mediation of risk-taking propensity is significant in all the cases except for integrator and firm financial efficiency. The researcher has adopted the latest and useful tools and techniques for exploring the problem. This study is a valuable addition. It is practically inducing the higher management and CEOs to follow the high-risk and high return concept while implementing the organizations' management accounting system. This study is also helpful for organisations that are willing to enhance financial efficiency by employing novel methods.
Keywords: 650; CEO; risk-taking propensity; firm financial efficiency; management accounting system